INFLUENCE OF MATERIAL PARAMETER MISMATCH ON CRACK PROPAGATION IN COMPOSITE LAMINATES - LI YouTang; YANG Jia; ZHANG ZhanTao (Jixie qiangdu)
The propagation path of cracks perpendicular to the interface of composite laminates usually takes many forms. By analyzing the stress field of crack tip during crack propagation, the driving force of crack tip is determined, in this way, the crack propagation path is analyzed. This article’s research object is the titanium-steel（TA2-Q235 B） composite laminate, a commonly used material for pressure vessels, the influence of the mismatch of elastic modulus and strength of the two materials on crack propagation is discussed by numerical analysis. The analysis results show that both two factors have a certain degree of promotion or inhibition of crack growth. When the crack propagates from a high-strength material to a low-strength material, the crack propagation rate increased and conversely decreased; when the crack propagates from a high elastic modulus material to a low elastic modulus material, the crack propagation rate increased and conversely decreased. No matter which direction the crack propagates from, the closer it is to the interface, the more obvious its effect will be. When the crack propagates to the interface, the crack propagation rate will decrease, or crack arrest will occur.